1990
DOI: 10.1111/j.1346-8138.1990.tb01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Elevated Serum LDH (Lactate Dehydrogenase) Activity in Atopic Dermatitis

Abstract: Serum lactate dehydrogenase activity (LDH) was elevated in most cases with the severe type of atopic dermatitis (AD). We examined whether LDH correlated specifically with the clinical courses and the severity of AD skin eruptions. Blood eosinophil numbers (Eo), LDH and its isoenzymes, and serum IgE (IgE) levels in eighty patients with AD were measured before and after treatment. In improved groups, Eo and LDH decreased or returned to normal values after treatment. In contrast, both levels increased in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 10 publications
6
46
0
Order By: Relevance
“…Because TARC is produced by T cells, the association between TARC and IL-18 levels suggests involvement of an aberrant adaptive immune response in our adult AD patients. We also found a strong association between serum IL-18 and LDH levels, as in a previous study [21]. LDH is an enzyme that is widely distributed in tissues, including the skin, and is generally elevated due to various disease processes.…”
Section: Discussionsupporting
confidence: 69%
“…Because TARC is produced by T cells, the association between TARC and IL-18 levels suggests involvement of an aberrant adaptive immune response in our adult AD patients. We also found a strong association between serum IL-18 and LDH levels, as in a previous study [21]. LDH is an enzyme that is widely distributed in tissues, including the skin, and is generally elevated due to various disease processes.…”
Section: Discussionsupporting
confidence: 69%
“…3,4 All other mean laboratory values were within the reference range during the study and showed no marked changes over time. One patient experienced an increase in transaminase levels that resolved before treatment discontinuation.…”
Section: Statistical Analysesmentioning
confidence: 78%
“…Immunologic states of AD patients are generally determined by measuring some blood parameters, such as the eosinophil number and the serum levels of total IgE and lactate dehydrogenase (LDH), the latter of which is released from impaired skin. These measurements also differently reflect the severity of AD [9]. Taken together, it still remains difficult to evaluate the severity of skin inflammation correctly and objectively.…”
Section: Introductionmentioning
confidence: 99%